Suppose x and y are two POSITIVE numbers so that -x and -y are negative.
Then a negative minus a negative = (-x) - (-y) = -x +y
If x > y the answer is negative
If x = y the answer is zero
If x < y the answer is positive
8 minus negative three or 8--3 equal positive 11. The double negative converts the minus sign into a plus sign and the negative into a positive.
-10 minus -10 is 0.
0 minus negative 6 is equal to 6.
-8 - (-13) = - 8 + 13 = +5 ( minus a minus is a plus)
4
no it equals a positive
8 minus negative three or 8--3 equal positive 11. The double negative converts the minus sign into a plus sign and the negative into a positive.
-12 minus -6 is -6
-10 minus -10 is 0.
yes
0 minus negative 6 is equal to 6.
-8 - (-13) = - 8 + 13 = +5 ( minus a minus is a plus)
negative 5
4
A negative number minus a positive number will always be a negative number.
Seven minus negative two times negative 4 is equal to -1
negative.